Lean Manufacturing Analysis with Waste Assessment Model (WAM) Approach to Reduce Critical Waste in the Production Process of Woven Sarong CV. XYZ - Raihan Rahmadianto; Joumil Aidil Saifuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The manufacturing industry faces challenges to improve efficiency and productivity amid increasingly fierce global competition. This study aims to analyze waste in the sarong weaving production process at CV. XYZ is using the Lean Manufacturing approach with the Waste Assessment Model (WAM) method. The results showed that the two most critical types of waste were transportation (20.95%) and inventory (20.64%). The root causes of transportation waste include inefficient fabric movement and narrow transportation lanes, while inventory waste is caused by the accumulation of goods in process (WIP) and the policy of purchasing raw materials in large quantities. The proposed improvements include layout optimization, efficient means of transportation, inventory management training, and line balancing implementation. The recommendations are projected to reduce production lead time by 13.60%, from 1,265 minutes to 1,093 minutes. This research makes a significant contribution to the application of Lean Manufacturing in the traditional textile industry.